Differences In Left Tilt Position With And Without Use Of Peanut Ball On The Length Of Labor Process In The 1st Stage In The Working Area Of The Panggungrejo Health Centre Blitar District - Natalia, Shanty; Shanty Trimukti Sayekti; Stevani Basuki Putri; Miftakhur Rohmah (Journal for Quality in Women's Health, 2024)
Background : Giving birth naturally is every pregnant mother hope, some cases required minimal medical intervention. Method : Pre-experimental research design with 2 treatment groups. The population all 1st stage labor mothers in Panggungrejo Health Center is 30 people. Result : The length of 1st stage labor oblique position without peanut ball was almost all respondents, namely 12 (80%) in the normal category. Analysis : There is difference the length labor in the 1st stage labor in side position with and without the use of peanut balls in Panggungrejo Health Center, Blitar Regency.  Conclution : Using peanut ball by adjusting the mother's position during labor can reduce pain, strengthen uterine contractions and allow normal fetal descent to speed up the length of the first stage of labor.